The Relationship Between Pain Intensity and Stress Level on Sleep Quality Among Junior High School Girls with Primary Dysmenorrhea: A Systematic Literature Review - Cyndi Yuliana; Sri Novia Fauza (Green Publisher Indonesia, 2026)
Early adolescence, especially at junior high school age, is a critical period of neurobiological and hormonal development. Primary dysmenorrhea, characterized by cramping pain in the lower abdomen without pelvic pathology, is the most common gynecological complaint in this population. This condition is often underestimated despite having significant systemic impacts, including severe sleep disturbances and increased psychological stress. This systematic review aimed to comprehensively analyze the relationship between menstrual pain intensity and psychological stress levels and sleep quality in adolescent girls with primary dysmenorrhea, with a special focus on the implications for adolescent health in the school environment. This study used a Systematic Literature Review (SLR) design with the PRISMA 2020 protocol. Ten studies that met the inclusion criteria, involving a total of more than 6,000 participants from different countries, including Indonesia, South Korea, China, the United States, India, Turkey, and Brazil, were qualitatively analyzed. Data synthesis showed a strong linear relationship in which high pain intensity (NRS ≥ 7) significantly predicted poor sleep quality (PSQI > 5) and impaired sleep efficiency. Adolescents with severe dysmenorrhea reported shorter sleep duration, prolonged sleep latency, and sleep fragmentation. On the other hand, psychological stress was identified as an independent variable and a crucial mediator; high stress levels, measured by DASS-21 or PSS, correlated with increased pain perception and decreased sleep quality. Longitudinal studies show that the transition to menarche at an early age exacerbates circadian rhythm disorders, including social jetlag, which are further worsened by menstrual pain.